NoSQL Databases Explored: A Comprehensive Study of Columnar, Graph, and Document-Based Approaches - Pradeep Bhosale (North American Journal of Engineering Research, 2022)
As data volumes, velocity, and variety rapidly expand, NoSQL databases have gained prominence for their ability to scale horizontally and handle flexible schemas. This paper provides a comprehensive study of three major NoSQL categories: columnar (column-family), graph, and document-based databases. While each addresses limitations of traditional relational models, they differ in data modeling, query paradigms, concurrency handling, and typical use cases. We begin by positioning NoSQL within the broader database evolution and analyzing why organizations turn to NoSQL solutions, especially in a microservices or big data ecosystem. Then, we delve into the design fundamentals of columnar (such as Cassandra, HBase), graph (Neo4j, JanusGraph), and document (MongoDB, CouchDB) stores, contrasting how each organizes data, ensures consistency, and scales horizontally. We also highlight key architectural patterns from CAP theorem trade-offs to advanced indexing and replication strategies along with performance benchmarks and references from real-world deployments. Through tables, diagrams, code snippets, and best practices, we clarify when to adopt each NoSQL category, the anti-patterns (e.g., misusing graph queries for purely relational tasks), and how to harness partitioning or eventual consistency effectively. Ultimately, this paper aims to guide architects, data engineers, and software practitioners seeking robust, horizontally scalable data solutions beyond the constraints of traditional relational databases